Criteria and non-criteria anti-phospholipid antibodies in the different clinical forms of antiphospholipid syndrome - Cabrera-Marante, Oscar; Pleguezuelo, Daniel; Garcinuño, Sara; Naranjo, Laura; Díaz-Simón, Raquel; Gil-Etayo, Francisco Javier; Zafra, Denis; Lozano-Morillo, Fernando; Morillas, Luis; Abad, Magdalena; Villar, Olga; Martínez-Salio, Antonio; et al. (Frontiers in Immunology, 2025)
IntroductionAntiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by thrombotic symptoms (venous, arterial, or small vessels) and/or gestational morbidity in patients carrying antiphospholipid antibodies (aPLs). Criteria aPLs include anti-cardiolipin antibodies, anti-beta 2 glycoprotein I (aB2GPI) antibodies of the IgG or IgM isotypes, and lupus anticoagulant (LA). However, there are aPLs that are associated with APS events but are not included in the criteria (extra-criteria). The aim of this study is to evaluate the prevalence and association of criteria and extra-criteria aPLs with APS clinical events.MethodsA total of 838 patients with clinical manifestations of APS were studied. In total, 715 presented with vascular manifestations, and 130 presented with obstetric morbidity. We measured levels of criteria aPLs, and the extra-criteria aPLs determined were anti-phosphatidylserine/prothrombin (aPS/PT) of IgG and IgM isotypes and aB2GPI IgA.ResultsClassic aPL, aPS/PT, and aB2GPI IgA positivity showed a significant and independent association with thrombosis (OR: 2.40, 2.36, and 2.53 respectively). IgA aB2GP1 was the only aPL significantly associated with the five types of thrombotic events (venous thrombosis, pulmonary embolism, stroke, acute myocardial infarction, and arterial thrombosis). Regarding obstetric APS, the most relevant antibodies were classic aPL of IgM isotype (OR: 36.04) and aPS/PT of both isotypes (OR: 4.4). The other aPL studied did not show association in multivariate analysis.DiscussionThe degree of clinical association for each group of aPLs was different depending on the form of presentation (vascular or obstetric) and the presence or absence of autoimmune diseases. Moreover, a fair level of agreement between LA and aPS/PT positivity was found; therefore, aPS/PT should not be referred to as a surrogate marker of LA.